Neutrophil Extracellular Traps Caused by Gut Leakage Trigger the Autoimmune Response in Nonobese Diabetic Mice - You, Qi; Shen, Yiming; Wu, Yiling; Li, Yuyan; Liu, Chang; Huang, Fengjie; Gu, Harvest F.; Wu, Jie (Frontiers in Immunology, 2022)
Increased formation of neutrophil extracellular traps (NETs) is associated with gut leakage in type 1 diabetes (T1D). To explore the mechanism of how enteropathy exacerbated by NETs triggers pancreatic autoimmunity in T1D, we carried out a correlation analysis for NET formation with gut barrier functions and autoimmunity in nonobese diabetic (NOD) mice. Inducing chronic colitis or knocking out of peptidyl arginine deiminase type 4 (PAD4) in NOD mice were used to further study the effect of NET formation on the progression of T1D. Microbial alterations in Deferribacteres and Proteobacteria, along with the loss of gut barrier function, were found to be associated with increased endotoxin and abnormal formation of NETs in NOD mice. Both DSS-induced colitis and knockout of PAD4 in NOD mice indicated that PAD4-dependent NET formation was involved in the aggravation of gut barrier dysfunction, the production of autoantibodies, and the activation of enteric autoimmune T cells, which then migrated to pancreatic lymph nodes (PLNs) and caused self-damage. The current study thus provides evidence that PAD4-dependent NET formation is engaged in leaky gut triggering pancreatic autoimmunity and suggests that either degradation of NETs or inhibition of NET formation may be helpful for innovative therapeutic interventions in T1D.